2021
DOI: 10.1097/01.jaa.0000758220.38067.49
|View full text |Cite
|
Sign up to set email alerts
|

A physician associate-led clinic for people with severe mental illness in the United Kingdom

Abstract: Objective: To evaluate an enhanced physical health clinic led by physician associates (PAs) for patients with severe mental illness. Methods: A guidance and data collection tool was developed to support and document the outcomes of the PA-led enhanced physical health clinic. Results: The clinic led to diagnoses of diabetes, hyperlipidemia, and hematologic abnormalities. One patient was started on metformin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…A 2021 article profiled a PA-led clinic that focused on treating physical illness concerns, such as metabolic complications of psychotropic medications in patients diagnosed with severe mental illness. 23 The study found that PAs can be effectively integrated into multidisciplinary teams and provide adequate care to patient populations with severe mental illnesses. The study highlights the holistic level of healthcare that PAs can provide in mental health care settings.…”
Section: Evidence From Other Contextsmentioning
confidence: 94%
See 3 more Smart Citations
“…A 2021 article profiled a PA-led clinic that focused on treating physical illness concerns, such as metabolic complications of psychotropic medications in patients diagnosed with severe mental illness. 23 The study found that PAs can be effectively integrated into multidisciplinary teams and provide adequate care to patient populations with severe mental illnesses. The study highlights the holistic level of healthcare that PAs can provide in mental health care settings.…”
Section: Evidence From Other Contextsmentioning
confidence: 94%
“…Further evidence of successful PA integration into psychiatry/mental health care fields can be found in the United Kingdom. A 2021 article profiled a PA-led clinic that focused on treating physical illness concerns, such as metabolic complications of psychotropic medications in patients diagnosed with severe mental illness 23. The study found that PAs can be effectively integrated into multidisciplinary teams and provide adequate care to patient populations with severe mental illnesses.…”
Section: Evidence From Other Contextsmentioning
confidence: 99%
See 2 more Smart Citations